2005
DOI: 10.1080/j.0001-6349.2005.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Methadone maintenance program in pregnancy in a Swiss perinatal center (II): neonatal outcome and social resources

Abstract: Background: The aim of the study was to analyze the neonatal impact of a methadone maintenance program in pregnancy, and the social resources of the families involved. Methods: Descriptive analysis of neonatal data in live births after 24 weeks of gestation in pregnant women enrolled in a methadone maintenance program. The data of 86 babies were analyzed. Results: Median gestational age was 38 0 / 7 (31-41) weeks; 21 babies (24%) were premature. Median birthweight was 2662 (1340-4050) g; 27% of babies were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 18 publications
1
46
2
1
Order By: Relevance
“…Polydrug use was common, despite an active methadone programme. This trend is similar to that noted in other studies [1,2,9,24].…”
Section: Discussionsupporting
confidence: 92%
“…Polydrug use was common, despite an active methadone programme. This trend is similar to that noted in other studies [1,2,9,24].…”
Section: Discussionsupporting
confidence: 92%
“…Brown et al (1998), reporting on 32 MMT pregnancies, found three major congenital abnormalities, two of which were fatal: a cardiac anomaly and a diaphragmatic hernia (p<0.001). In the study published by Arlettaz et al (2005), fourteen congenital malformations were described in 12 of 78 newborns (15%). One newborn with multiple malformations died at 1 year of age.…”
Section: Teratogenecitymentioning
confidence: 97%
“…Duration of hospitalization ranged from 8 to 105 days (median 25 days). Arlettaz et al (2005) in a study of the impact on neonates of MMT in pregnancy analyzed 86 live births of over 24 weeks gestation and found that 49 of 79 newborns (62%) born to mothers receiving MMT required pharmacologic treatment for NAS; and that the incidence of NAS was proportional to the dose of maternal methadone. At methadone doses below 30 mg/day, 43% of newborns required treatment.…”
Section: Neonatal Abstinence Syndromementioning
confidence: 98%
“…Nachteil der Methadonsubstitution während der Schwangerschaft ist die Entwicklung eines neonatalen Entzugssyndroms (NAS) in 30 -80 % der Fälle [4,15]. Das NAS, das seinen Gipfel etwa 48 -72 Stunden postnatal erreicht, wird in seiner Symptomatik im Allgemeinen nach einem Score nach Finnegan beurteilt [16].…”
Section: Stillen Und Das Neonatale Entzugssyndromunclassified